Dynamic modeling and control of engineering systems - Shearer, J. Lowen (Prentice Hall, 1997)
This book presents a comprehensive treatment of the analysis of lumped parameter physical systems. The first portion of the book deals with the fundamentals of dynamics system modeling including a discussion of mechanical systems (translational and rotational), analytical solutions of ordinary differential equations and a discussion of state space theory. This book includes treatment of both input/output and state space models, analogies between physical domains (mechanical, electrical, fluid, and thermal) with an emphasis on the appropriate physical laws, an in-depth discussion of mixed (multi-domain) systems, and a discussion of nonlinearities and linearization methods. Contains chapters on Discrete- Time systems and digital control. It also presents a discussion of transfer functions, stability, and feedback control. It provides specific examples and problems geared toward MATLAB and SIMULINK as well as example files and supplementary files to run with MATLAB and SIMULINK. A valuable reference book for engineering and computer professionals responsible for systems modeling.